Mathematical Laboratory: Semiotic mediation and cultural artefacts in the mathematics classroom - Bartolini Bussi, Maria G. (Teaching Mathematics and Computer Science, 2020)
Aim of this presentation is to summarize the influence of Tamas Varga on the Italian research and practice concerning didactics of mathematics since the 70s of the 20th centuries. While being in Budapest for the Conference I noticed that this influence was not known by most Hungarian mathematics educators. I guess that also in Italy, only the teacher educators of my generation know Varga’s influence on the teaching and learning of mathematics in primary school. Hence I start from a brief summary of development of mathematics curriculum in Italy (mainly in primary school) in the last decades of the 20th century. I focus some elements that may be connected with Varga’s influence and, later, some recent development of them.Subject Classification: 97G20, 97-U6, 97A40